Cardinalidad, ejemplo 2 - Chavarría-Molina, Jeffry (My University, 2018)
En este vídeo se presenta un segundo ejemplo de cálculo de cardinalidades sobre conjuntos, dados condiciones sobre las cardinalidades de éstos y algunas de sus operaciones.

This video presents a second example of calculation of cardinalities on sets, given conditions on their cardinalities and some of their operations.
Keywords: Conjuntos; Operaciones matemáticas; Cálculo; Matemáticas discretas; Sets; Mathematical operations; Calculus; Discrete mathematics